Protective Effects of Oxymatrine on Experimental Diabetic Nephropathy - Guo, Changrun; Han, Fengyu; Zhang, Chunfeng; Xiao, Wei; Yang, Zhonglin (Planta Medica, 2014)
Diabetic nephropathy, one of the most common and serious vascular complications of both type 1 and type 2 diabetes mellitus, has become a major contributor of end-stage renal failure. The aims of this study were to investigate the effects and possible underlying action mechanism(s) of oxymatrine on renal damage in diabetic rats. Diabetes was induced in male Sprague-Dawley rats by administering a high-fat diet and an intraperitoneal 30 mg/kg streptozotocin injection. The animals were treated orally with saline, metformin hydrochloride, and oxymatrine at 50, 100, and 150 mg/kg/day for 11 weeks. At the end of the treatment, renal tissue, blood, and urine samples were collected for histological and biochemical examination. The results revealed that oxymatrine significantly decreased blood glucose, urinary protein and albumin excretion, serum creatinine, and blood urea nitrogen in diabetic rats, and ameliorated diabetes-induced glomerular and tubular pathological changes. Furthermore, oxymatrine significantly prevented oxidative stress and reduced the contents of renal advanced glycation end products, transforming growth factor-β1, connective tissue growth factor, and inflammatory cytokines in diabetic rats. All these results indicate that oxymatrine has protective effects on experimental diabetic nephropathy by multiple mechanisms.
Keywords: oxymatrine; diabetic nephropathy; oxidative stress; TNF-α; TGF-β1; Sophora flavescens; Fabaceae